A new peat-associated omphalinoid species from Europe: Arrhenia turficola sp. nov. (Agaricomycetes, Agaricales, Hygrophoraceae) - Moreau, Pierre-Arthur; Corriol, Gilles; Vašutová, Martina; Bellanger, Jean-Michel (Phytotaxa, 2026)
A new peat-associated species of Arrhenia, A. turficola sp. nov., is described. Hitherto known from continental Europe, the species is likely widespread, but uncommon. ITS and LSU nrDNA sequences reveal that it forms a clade distant from that containing all previously known hygrophilous species. Comparisons with ecologically and morphologically similar species are also discussed. In particular, although its distinct grey colour recalls the terricolous A. griseopallida, the striate pileus is inconsistent with Desmazières’ protologue, and its morphological, ecological, and molecular features do not match any of the diverse modern interpretations of that name.